LOCAL PREDICTION OF VERY LARGE OIL AND GAS FIELDS ON THE SIBERIAN CRATON ACCORDING TO THE MORPHOSTRUCTURAL DATA - Vinogradoy Y.I.; Guberman S.A.; Dmitriyevskiy A.N.; Rantsman Y.Y.; Ulmasvay F.S. (My University, 1990)
The prediction of petroleum and natural gas fields (especially very large ones) is a very interesting scientific problem and a highly important economic tasks. Other publications by the present writers using examples from South America and West Siberia have shown the effectiveness of the method of local prediction of the very large oil and gas fields from morphostructural data, using recognition methods (probability of error less than 0.2, precision of prediction 75 km). This has created the basis for local prediction of oil and gas in one of the least thoroughly studied regions, East Siberia, where intensive oil and gas exploration has been carried out for a long time. The basis of local prediction is morphostructural zoning. To test the method, these same characteristics were used to predict large HC deposits in West Siberia. The results obtained provide the basis for applying the method to a new region, not for the purpose of testing it, but to obtain a reliable prediction of potential HC productivity. One such new region was the Siberian craton.